Pattern and predictors of sexual behaviour among adolescents in Ibadan, South West, Nigeria - Olorunsola AM; Muyibi SA; Irabor AE; Adetunji AA; Ismail WO; Ogunniyan T (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Background: Adolescents are usually strong and known for vitality but reproductive and sexual issues constitute challenges to their health and well- being. Sexual choices are controlled by interaction of factors surrounding the adolescents' existence. Aim: The study investigated the pattern and factors affecting sexual behaviour among adolescents in Ibadan, South West, Nigeria. Method: A cross sectional study was conducted among sexually active adolescents at two Family Medicine Practice Clinics after obtaining ethical approval. Data was collected on sexual behaviour, socio demographic and family characteristics using interviewer administered questionnaire. Data was analysed with SPSS version 18 and test of association was done using chi-square and multiple logistic regression at 5% level of significance.  Results: The mean age of sexual debut was 18.82 + 2.804 years, with age of onset being a year earlier among male respondents compared to females. Higher proportion of males (50.9%) had intercourse before age 16 and were involved in sex with multiple partners (71.2%). Females accounted more for inconsistent condom use (67.7%) and transactional sex (73.3%). Predictors of unsafe sexual behaviour were non- tertiary education (OR= 2.05, Confidence Interval: 1.096-3.848), lower social class OR: 2.721, Confidence Interval: 1.422-5.308 and conflict- oriented family types (OR= 1.894 Confidence Interval: 1.036-3.462). Conclusion: The findings showed different pattern of sexual behaviour among adolescents. Factors that predicted unsafe sexual practice were low education, poverty and family dysfunction. Ameliorating these factors will reduce risky sex pattern and related morbidities among adolescents' population.